Hormônios em furia : Desejo, curiosidade e expectativas sexuais entre adolescentes. - Oliveira, Tania Regia de (2013)
The theme of this thesis is Adolescent Sexuality, and has as main objective to understand the meanings that adolescents employ their practices affective / sexual, with the locus of research the city of Campina Grande, located in the state of Paraíba. The method I used face interviews, focus group worked with, texts sent by e-mail, and virtual interviews (by Facebook). As theoretical axes, broke the concepts of individual and society worked by Simmel (2006) and ELIAS (1994), in which individual characteristics are as relevant as the collective, and are in a constant process of interaction. Used the concept of adolescence as a concept is not widespread at a given time, or as a transition phase, but considering its procedural nature (Aries, 1981; ALTMANN, 2007; Featherstone, 1994; ABRAMO, 1997). Sexuality is analyzed according to the social constructivist approach (VANCE, 1995 and WEEKS, 2007), in their interaction with socialization with learning the subject (HEILBORN, 2004). Based on the understanding that sexual activity with a partner, with all the learning involved, begins in adolescence, parti understanding that this practice should be considered as a "marker" of this phase of the social life of individuals (MEINERZ, 2004 ), as a mediator of social relations among young people (Brandão, 2009). Sexuality is also focused on the theory of sexual scripting (GAGNON, 2006), which links the links between individual behavior and social influences more extensive.